Penerapan Restorative Justice dalam Penegakkan Hukum Pidana Anak Berdasarkan Undang-Undang Nomor 11 Tahun 2012 - Bambang Tri Suparyanto Nugroho; Gunawan Nachrawi; Adi Sujatno (Syntax Literate, 2023)
Children with all their definitions and definitions have different characteristics from adults, this is a starting point in viewing the rights and obligations for a child that will also affect his position before the law. In consideration of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, it is also stated that children are the trust and gift of God Almighty who has dignity and dignity as a whole person. To maintain their dignity and dignity, children are entitled to special protection, especially legal protection in the justice system. The concept and philosophy of criminal law and the juvenile criminal justice system that provides balanced protection of the rights and interests of perpetrators and victims of criminal acts, society and the state, is currently known as restorative justice as a judicial concept that produces restorative justice. Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, hereinafter referred to as the Juvenile Criminal Justice System Law, when viewed from the philosophy underlying the birth of the juvenile justice law is because children have not been able to understand what they are doing and prioritize the best interests of children and in accordance with the 1990 Convention on the Rights of the Child ratified by Indonesia as a member of the United Nations (UN) through Presidential Decree Number 36 of 1990 states that Crime is a last resort because children are assets of the nation and the next generation, based on this law the government makes legal efforts to find the best way for children by issuing a regulation called Supreme Court regulation number 4 of 2014 concerning Guidelines for the implementation of diversion in the juvenile criminal justice system